Assembly of Enantioenriched cis‐3a, 8a‐Hexahydropyrrolo[2, 3‐b]indole Scaffolds by Silver(I)‐Catalyzed Asymmetric Domino Reaction of Isocyanoacetates in the Presence of Cinchona‐Derived Chiral Phosphorus Ligands. Issue 6 (11th February 2016) - Cheng, Hengguang; Zhang, Runmei; Yang, Shiwei; Wang, Min; Zeng, Xiaofei; Xie, Lingjie; Xie, Chunsong; Wu, Jing; Zhong, Guofu
Abstract: By using Cinchona ‐derived chiral phosphines as catalytic ligands, enantioenriched cis ‐3a, 8a‐hexahydropyrrolo[2, 3‐ b ]indoles ( ent ‐HPIs), which are core scaffolds in a large array of biologically active natural products, can be convergently assembled under mild conditions through the silver(I)‐catalyzed asymmetric domino reaction of readily available isocyanoacetates and 2‐(2‐aminophenyl)acrylates. Various functionalities can be tolerated in the reaction, affording enantioenriched HPIs in high overall yields and good enantioselectivities (up to 92% ee s). Abstract :